Association Between Working Hours, Length of Employment, and Repetitive Movements with Carpal Tunnel Syndrome Complaints Among Grinding Workers at Company X, Batam City, Indonesia, in 2024 - Kartika Wijaya, Juhanda; Noviyanti, Noviyanti; Maulina, Diina; Monalisa, Monalisa (Rifa'Institute, 2025)
Introduction: The prevalence of MSDs disorders out of the average occupational disease is nearly 50%. MSDs include several types, one of which is carpal tunnel syndrome. Objective: The purpose of the study was to determine the frequency distribution of work duration, work period and repetitive movements in grinding workers at PT X Batam City in 2024 and to determine the relationship between work duration, work period and repetitive movements with the occurrence of carpal tunnel syndrome complaints in grinding workers at PT X Batam City in 2024. Method: Research methodology This type of research is quantitative research with a cross sectional study design. Data collection was carried out by distributing questionnaires and observing repetitive movements of grinding work. Result and Discussion: The results of the study showed that the majority of workers with work duration > 8 hours per day (64.2%), work period > 2 years (89.8%) and repetitive movements ? 20 times per minute (66%), showed a significant relationship between work duration, work period and repetitive motion with P_value = 0.000, p < a (? = 0.05) to complaints of carpal tunnel syndrome. Conclusion: Suggestions for setting working hours and providing additional breaks for workers with a long work period to reduce tension on the wrist